The Genesis of Young Ottoman Thought: A Study in the Modernization of nrkish Political Ideas by Serif Madin, (Syracuse: Syracuse Univenity Pns, 2000, xii+456 pp.) (American Journal of Islam and Society, 2001)
This book, originally published in 1962, has now become a classic on the historyof modemTurkish political thought, whose beginning is usually traced back to theT-t period (1836-1878), the most turbulent and crucial period of modemTurkish history. Serif Mardin, the famous Turkish historian and political scientist,is like a household name to those interested in modern Ottoman and Turkishintellectual history. In his numerous books and articles, which followed thepublication of the present work, Mardin took the herculean task of unearthing theparameters of modem Turkish thought with an almost solitary conscience. It issimply impossible to have a discussion about Islam and Turkish society, socialchange, modernization or secularization without referring to Mardin’s work,which is woven around a string of ideas, concepts and analytical tools, all of whichenable him to see the realities of Turkey and the modem Islamic world both fromwithin and from without. His more recent Relwon and Social change in Twkey:’ c irhe of&aYuzaman Said Nuni (New York: SUNY Press, 1989),w hich is thesingle most important book written in English on Said Nursi, the founder of theNurcu movement in Turkey, is the result of the same set of principles Mardin hasadopted throughout his career: diligent scholarship, resistance to fads, and willingnessto understand before passing any judgements on his subject.The present work under review touches upon the most sensitive and crucialperiod of modem Turkish history, viz., the end of the Ottoman era and the establishmentof the modem Turkish Republic. Mardin’s exclusive emphasis is on theTanzirnat period, and the figures that laid the intellectual foundations of it. Thesignificance of this period can hardly be overemphasized, not only for Turkish historybut also for the rest of the Islamic world. It was in this period that a wholegeneration of ottoman intellectuals, from right to left, was faced with the historictask of confronting modem western civilization in the profoundest sense of theterm, and their successes and failures set the agenda for the modem intellectualhistory of Turkey for decades to follow. Their troublesome journey was shaped bythe historical setting, in which they came to terms with such questions as modernism,secularism, westernization, nationalism, Islam, society, science, tradition,and a host of other issues that continue to haunt the minds of the Islamic worldtoday. Their trial, however, was linked to the rest of the members of the Islamicworld in ways, as the present work under review shows, more important than isusually thought, and this issue, namely the place of ottoman intellectual historywithin the larger context of modem klamic thought, has not been resolved. In this ...